Planetarium di Kota Makassar - Budikusuma, Rifki; Ansarullah, Ansarullah; Alimuddin, Aris (Universitas Muslim Indonesia, 2025)
Since ancient times, humans have lived on earth with the sky above them. In a clear sky, we can see celestial bodies in the form of planets, sun, moon, stars, or at a certain time natural phenomena such as meteors. Astronomy as the earliest science in human civilization has been known about 3000 years before the ancient Babylonian era, on the holy book of Al-Quran also found various information about the universe, 20 verses mention the word sun, 463 verses that mention the earth, and 5 verses that mention the moon. Not to mention the verses that describe the sky, the changes of day and night, and the verses that mention the stars. Planetarium as one of the facilities in science, astronomy basically functions as entertainment and education or we can say edutainment, with procurement of supporting facilities, namely in the form of an observatory. Based on the 2006 curriculum and the 2013 curriculum which explains that astronomy is studied in grades I, II and IV of elementary school, and physics at junior high school up to high school and the effective learning methods is by see and feel it for yourself